Writing conscience and the nation in revolutionary England - Iacono Lobo, Giuseppina, 1980- (University of Toronto Press, 2017)
Examining works by well-known figures of the English Revolution, including John Milton, Oliver Cromwell, Margaret Fell Fox, Lucy Hutchinson, Thomas Hobbes, and King Charles I, Giuseppina Iacono Lobo presents the first comprehensive study of conscience during this crucial and turbulent period.